The Federal Republic of Germany and the first Indochina War (1946-1954) - Dao, Duc Thuan; Justus Liebig University Giessen (My University, 2012)
The entire relations between the decolonization issue and the European integration has not been studied well so far, especially from the Asian perspective. Besides, European integration was not only an internal European affair, it was deeply affected or even sped up by the changes in the relations between in colonial centers and peripheries or even West Europe and the colonized world in total. For this reason, the first Indochina War in my research may serve as one of the striking cases to be investigated. Together with the end of the World War II, other events occurring in the late 1940s and early 1950s such as the establishment of the People s Republic of China (1949), the outbreak of the Korean War (1950), the emergence of the Cold War, etc have changed the entire structure of the world politics and international relations. Under this circumstance, the relation between France and West Germany was indeed to be re-defined. As a matter of fact, the colonized world was also much influenced. Within this context, European framework at that time was not shaped yet and Europe was still on the move of economic and political reconstruction. Although main colonial powers (France and Britain) were weakened after the World War II, France was in dilemma in between recolonization and European integration. To some extent, France ignored the de facto decolonization that would be unavoidable tendency all over the colonized world. In many French leaders minds, recolonization and thus, owning colonies are considered a part of their foreign policy and empire. For West Germany, after the formation of the Federal Republic, top leaders or representatives of different political groups were searching for the reorganization of their state which would be different from what had existed in the Weimar Republic and the Third Reich. Additionally, political ideas of European policy were not yet set up in West Germany. The problem is that under what dimension the Federal Republic should be or should push forwards? How diverse political parties should act in future? How the problem of the German reunification should be resolved?All the above-mentioned issues set the basis for the official attitudes of the federal government headed by Dr. Konrad Adenauer and other political and religious groups. The first Indochina War produced a huge media event in West Germany in the early 1950s. Accordingly, the West German media reflected the public view of the West German society and culture in the early 1950s on happenings inside and outside Europe. These views may help West German politicians and the society re-define the entire position of West Germany in the 1950s and the decades that followed. Rooted from the impacts of the French decolonization in Indochina and other crucial events in Europe and Africa, some lessons-learnt were figured out for West Germany: firstly, the German-Franco reconciliation (Élysée Treaty 1963); secondly, West German (further) integration into the Western institutions; thirdly, the West German policy towards the Third World countries; fourthly, the emergence of the New Left in the FRG. Finally, by giving a humble explanation to postcolonial theory, in my thesis the French decolonization in Indochina was a tool to understand the relations between France and West Germany. They were the fundament for a common interpretation of defeat and losses which deeply influenced the interactions of the contemporary leading politicians for Germany, the collapse of its world power aspirations and the establishment of more than one German state, for France the defeat against Germany and the following collapse of its colonial empire. For that, decolonization was used to explore new interactions of the world entangled . The influence of the French decolonization in Indochina on France, West Germany in particular and on Europe in general as the decolonization has sped up the process of the European integration since the 1950s.
Die Bundesrepublik Deutschland und der erste Indochinakrieg (1946-1954)
Keywords: Der erste Indochinakrieg; Vietnam; französische Entkolonialisierung; Westdeutschland; europäische Integration; The first Indochina War; Vietnam; French decolonization; West Germany; European integration; ddc:900